Knowledge, Attitudes and Practices of Women Regarding Physical Activity during Pregnancy and its Related Factors - Ranaa Abdulmohsen Bin Jaman Alharbi; Amel Hamed Ail Alkhasem; Huda Ahmed H Alhebshi; Amal Saeed Nasir Aldosary; Awatef Marzoq Alnader; Latifah Matoq Aziz Aldadi; Nouf Abdulrahman Abdullah Melebary; Suoad Ibrahem Ahmed fallatah; Manal Omar Hasan Rawass; Jalila Saeed Apdurapo Altakroni (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The knowledge, attitudes, and practices (KAP) of women regarding physical activity (PA) during pregnancy and the factors influencing these aspects are crucial for improving maternal and fetal health outcomes. Understanding these dimensions helps identify gaps in education, cultural influences, barriers to engagement, and strategies for promoting physical activity during pregnancy.Physical activity consists of planned, repetitive, and intentional movements that reduce the risk of pregnancy-related complications. Worldwide, there is a high rate of physical inactivity during pregnancy.While awareness about the benefits of physical activity during pregnancy is growing, many women in Saudi Arabia still lack comprehensive knowledge about the guidelines and safety precautions for exercise during pregnancy. The aim of the study:to assess women’s knowledge, attitude, and practice toward physical activity during pregnancy and its related factors among antenatal care. Method: A cross-sectional study was conducted among 614 pregnant women receiving antenatal care fromFebruaryto April 2024. The study participants were selected using systematic random sampling technique. Data were collected using a pretested, face-to-face interviewer-administered and semi-structured questionnaire. The data were cleaned, coded, and entered into Epi Data (version 4.6) and analyzed using SPSS (version 28). Bivariate and multivariate binary logistic regression analyses were performed to identify factors associated with knowledge, attitude, and practice toward physical activity during pregnancy. Variables with a P value of <2 in the bivariate analysis were transferred to the multivariate analysis. Finally, the adjusted odds ratio and 95% conﬁdence interval with a P value of <.05 in the multivariate analysis were considered statistically signiﬁcant. Results: The study found that 56.3% of participants had good knowledge, 51.5% of participants had a favorable attitude, and 32.2% of participants practiced physical activity during pregnancy. Age, educational level, and heard about physical activity during pregnancy were positively associated with pregnant women’s knowledge and attitude. In addition, age, antenatal care follow-up, no history of abortion, ever done physical exercise before becoming pregnant, and good knowledge were positively associated with pregnant women’s practice of physical activity during pregnancy. Conclusion: Our ﬁndings indicate that approximately half of the participants had good knowledge and a favorable attitude. However,almost one-third of the participants practiced physical activity during their pregnancy. It is recommended that antenatal care providers advise pregnant women to strengthen their antenatal care follow-up and offer health education and counseling about the beneﬁts of physical activity during pregnancy.